An intelligent nanodevice based on the synergistic effect of telomerase-triggered photodynamic therapy and gene-silencing for precise cancer cell therapy. Issue 18 (6th May 2020) - Yi, Jin-Tao; Pan, Qing-Shan; Liu, Chang; Hu, Yan-Lei; Chen, Ting-Ting; Chu, Xia
Abstract : An intelligent DNA-MnO2 nanodevice was designed for the telomerase-activated photodynamic (PDT) and gene-silencing synergistic effect for cancer cells theranostic. Abstract : The development of intelligent and precise cancer therapy systems that enable accurate diagnosis and specific elimination of cancer cells while protecting normal cells to improve the safety and effectiveness of the treatment is still a challenge. Herein, we report a novel activatable nanodevice for precise cancer therapy. The nanodevice is constructed by adsorbing a DNA duplex probe onto MnO2 nanosheets. After cellular uptake, the DNA duplex probe undergoes telomerase-triggered conformation switching, resulting in a Ce6 "turn-on" signal for the identification of cancer cells. Furthermore, Deoxyribozyme (DNAzyme) is activated to catalyse the cleavage of survivin mRNA, actualizing a precise synergistic therapy in cancer cells involving photodynamic therapy and gene-silencing. The MnO2 nanosheets provide Mn 2+ for the DNAzyme and relieve hypoxia to improve the efficiency of the photodynamic therapy. Live cell studies reveal that this nanodevice can diagnose cancer cells and specifically eliminate them without harming normal cells, so making the treatment safer and more effective. The developed DNA-MnO2 nanodevice provides a valuable and general platform for precise cancer therapy.